PRACTICE OF HEALTH EDUCATION BY NURSES AND ASSOCIATED FACTORS AT PHU NINH REGIONAL HEALTH CENTER, PHU THO PROVINCE IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the current status of nurses’ health education skills practice and associated factors at Phu Ninh regional Health Center, Phu Tho province in 2025.Subjects and methods: A cross-sectional descriptive study was conducted among 65 nurses through direct observation of nurses providing health education to patients and their caregivers at Phu Ninh regional Health Center.Results: The study involving 65 nurses showed that 84.6% were female and 15.4% were male; 32.3% held a bachelor’s degree, while 67.7% had a college degree. Overall, 69.2% of nurses demonstrated satisfactory health education practices, whereas 30.8% did not meet the required standard. Nurses performed well in basic communication skills, including greetings, professional attitude, and the use of understandable language (≥ 90%). However, limitations were identified in more advanced aspects, such as assessing patients’ needs (13.8%), discussing solutions (23.1%), using educational support materials (18.5%), checking patients’ understanding (10.8%), and summarizing key points at the end of counseling sessions (4.6%). Statistically significant factors associated with health education practice included professional qualifications, years of work experience, number of patients cared for per day, and supervisory activities within departments (p < 0.05).Conclusion: Health education practice among nurses reached a relatively satisfactory level (69.2%); however, advanced counseling skills and the closing phase of counseling sessions require further improvement. Practice was significantly influenced by educational qualifications, professional experience, workload, and supervisory activities. Therefore, enhanced training and management strategies are needed to improve the effectiveness of health education activities.
Keywords: Practice, nurses, health education, counseling.